PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MANAJEMEN BERBASIS SEKOLAH DI SD AL-FITYAN SCHOOL TANGERANG: PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MANAJEMEN BERBASIS SEKOLAH DI SD AL-FITYAN SCHOOL TANGERANG - Siti Munawati (ISLAMIKA, 2023)
Abstract School-based management is an education delivery model that provides flexibility to schools to compile and implement education programs in schools according to their needs through the empowerment of existing resources including community participation so that it better reflects efforts to improve the delivery of education delivery services in a democratic, transparent and accountable manner in real terms to achieve the goal of more efficient education and effective without prejudice to the objectives of National Education. SD Al-Fityan school is flexible in managing, organizing, utilizing school resources in a transparent manner, accountability, making decisions with school residents and being responsible in its performance. This type of research is descriptive qualitative with data sources from representatives. Descriptive qualitative research is research that explains a phenomenon concretely, actually, and realistically. The data collection techniques used in this study were interviews, observations and documentation of data validation. This qualitative research uses methods based on the philosophy of post-positivism, to examine the natural condition of objects, focusing more on meaning than generalization. School Based Management (SBM) There is some evidence of the components of School management consisting of student management, curriculum management, finance, personnel, facilities and infrastructure. SD Al-Fityan school is flexible in managing, organizing, utilizing school resources in a transparent manner, accountability, making decisions with school residents and being responsible in its performance. Keywords: Democratic, Organizing, Model, Transparent